RELATIONSHIP WATER QUALITY WITH STRUCTURE OF FISH COMMUNITIES CAPTURED IN LAKE HANJALUTUNG - Ummi Suraya; Muhamad Noor Yasin; Irawadi Gunawan (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2022)
This study aims to determine the water quality and structure of the fish community as well as the relationship between water quality and the structure of the fish community in Lake Hanjalutung. This research was conducted from September to November 2021 at Lake Hanjalutung, Palangka Raya City. The method used is direct observation or (survey) directly to Lake Hanjalutung. The results of the study obtained temperature values of 28.33oC- 29.40 oC, brightness 22.83cm- 24.50 cm, depth 0.42m- 1.17m, pH 5.67-6.07, DO 2.91 mg / l - 3.51mg / l, BOD 1.93mg / l-10.30mg / l, and COD 38.40mg / l-85.33 mg / l. The number of fish species caught in Lake Hanjalutung using gill nets is 816 individuals, 17 species, and 9 families. The results of the data analysis showed that the diversity index value ranged from 1.35-1.59 in the medium category, the uniformity index value ranged from 0.63-0.94 in the high category and the dominance index value ranged from 0.25-0.44 which means that no fish species dominated. Based on the results of the analysis using multiple linear regression, water quality parameters simultaneously have a relationship with the structure of fish communities, where the diversity index with values (sig. 0.016), the uniformity index with values (sig. 0.036) and the dominance index with values (sig. 0.038). Penelitian ini bertujuan untuk mengetahui kualitas air dan struktur komunitas ikan serta hubungan antara kulaitas air dengan struktur komunitas ikan di Danau Hanjalutung. Penelitian ini dilaksanakan pada bulan September sampai Nopember 2021 di Danau Hanjalutung Kota Palangka Raya. Metode yang digunakan adalah observasi langsung atau (survei) secara langsung ke Danau Hanjalutung. Hasil penelitian diperoleh nilai suhu 28,33oC- 29,40 oC, kecerahan 22,83cm- 24,50 cm, kedalaman 0,42m- 1,17m, pH 5,67-6,07, DO 2,91 mg/l - 3,51mg/l, BOD 1,93mg/l-10,30mg/l, dan COD 38,40mg/l-85,33 mg/l. Jumlah spesies ikan yang tertangkap di Danau Hanjalutung dengan menggunakan jaring insang sebanyak 816 individu, 17 spesies, dan 9 famili. Hasil analisis data menunjukkan nilai indeks keanekaragaman berkisar 1,35-1,59 dalam kategori sedang, nilai indeks keseragaman berkisar 0,63-0,94 dalam kategori tinggi dan nilai indeks dominasi berkisar 0,25-0,44 yang berarti tidak ada spesies ikan yang mendominasi. Berdasarkan hasil analisis menggunakan regresi linier berganda bahwa parameter kualitas air secara simultan memiliki hubungan dengan struktur komunitas ikan, dimana indeks keanekaragaman dengan nilai (sig. 0,016), indeks keseragaman denagn nilai (sig. 0,036) dan indeks dominasi dengan nilai (sig. 0,038).